311sp23final_sol

pdf

School

Rumson Fair Haven Reg H *

*We aren’t endorsed by this school

Course

311

Subject

Mathematics

Date

Nov 24, 2024

Type

pdf

Pages

7

Uploaded by CoachRiverTiger30

Report
Math 311 Final Exam Spring 2023 Fri May 5 No electronic devices are allowed. No collaboration is allowed. There are 10 pages and each page is worth 6 points, for a total of 60 points. 1. Direct Integration. Consider the equation x 00 ( t ) = t . (a) Find the general solution. Integrating twice gives x 00 ( t ) = t x 0 ( t ) = 1 2 t 2 + c 1 x ( t ) = 1 6 t 3 + c 1 t + c 2 for some constants c 1 , c 2 . (b) Find the solution with x (0) = 2 and x 0 (0) = 3. Substituting t = 0 in x 0 ( t ) gives x 0 (0) = 1 2 0 2 + c 1 3 = c 1 , and substituting t = 0 in x (0) gives x (0) = 1 6 t 3 + c 1 (0) + c 2 2 = c 2 , hence x ( t ) = 1 6 t 3 + 3 t + 2 . 2. Separation of Variables. Consider the equation dy/dx = x/y . (a) Use separation of variables to find the general solution. We have ydy = xdx Z y dy = Z x dx + C 1 2 y 2 = 1 2 x 2 + C y 2 = x 2 + D y = ± p x 2 + D for some constant D . 1
2 (b) Find the specific solution with y (2) = 4. Substituting x = 2 and y = 4 gives (4) 2 = (2) 2 + D 16 = 4 + D 12 = D, hence y ( x ) = ± p x 2 + 12 . 3. Logistic Growth. The logistic equation dy/dx = y (1 - y ) has general solution y ( x ) = 1 + e - x y (0) 1 - y (0) - 1 . (a) Sketch the slope field of the equation. (b) Sketch the solutions with initial conditions y (0) = 0 . 1, y (0) = 1 and y (0) = 2. 4. Damped Oscillations. Consider the equation x 00 ( t ) + 2 x 0 ( t ) + 2 x ( t ) = 0. (a) Find the general solution. We look for basic solutions of the form x ( t ) = e λt . Substituting gives λ 2 e λt + 2 λe λt + 2 e λt = 0 λ 2 + 2 λ + 2 = 0 λ = - 2 ± 4 - 8 2 = - 1 ± i. Hence the general solution is x ( t ) = c 1 e ( - 1+ i ) t + c 2 e ( - 1 - i ) t = e - t ( c 1 e it + c 2 e - it )
3 = e - t ( c 3 cos t + c 4 sin t ) for some constants c 3 , c 4 . (b) Find the specific solution with x (0) = 0 and x 0 (0) = 1. Substituting t = 0 in x ( t ) gives x (0) = e 0 ( c 3 1 + c 4 0) 0 = c 3 . Computing x 0 ( t ) and substituting t = 0 gives x 0 ( t ) = - e - t ( c 3 cos t + c 4 sin t ) + e - t ( - c 3 sin t + c 4 cos t ) x 0 (0) = - e 0 ( c 3 1 + c 4 0) + e 0 ( - c 3 0 + c 4 1) 1 = - c 3 + c 4 1 = - 0 + c 4 1 = c 4 , hence x ( t ) = e - t (0 cos t + 1 sin t ) = e - t sin t. 5. Undetermined Coefficients. Consider the equation x 00 ( t ) + x 0 ( t ) = t . (a) Find the general solution of the homogeneous equation x 00 ( t ) + x 0 ( t ) = 0. Substituting the guess x ( t ) = e λt gives λ 2 e λt + λe λt = 0 λ 2 + λ = 0 λ ( λ + 1) = 0 λ = 0 , - 1 . Hence the general solution of x 00 ( t ) + x 0 ( t ) = 0 is x ( t ) = c 1 e 0 t + c 2 e - 1 t = c 1 + c 2 e - t . (b) Find the general solution of the non-homogeneous equation x 00 ( t ) + x 0 ( t ) = t . Use the guess x p ( t ) = A + Bt + Ct 2 for the particular solution. To find a particular solution we substitute the guess x p ( t ) = A + Bt + Ct 2 : ( A + Bt + Ct 2 ) 00 + ( A + Bt + Ct 2 ) 0 = t 2 C + B + 2 Ct = t (2 C ) t + ( B + 2 C ) = 1 t + 0 . Comparing coefficients gives 2 C = 1 and B + 2 C = 0, hence C = 1 / 2 and B = - 2 C = - 1. The value of A is arbitrary. Let’s just take A = 0 to obtain the particular solution x p ( t ) = 0 - t + t 2 / 2 . Combining this with the homogeneous solution from part (a) gives the general solution x ( t ) = x c ( t ) + x p ( t ) = c 1 + c 2 e - t - t + t 2 / 2 .
Your preview ends here
Eager to read complete document? Join bartleby learn and gain access to the full version
  • Access to all documents
  • Unlimited textbook solutions
  • 24/7 expert homework help
4 6. Rules for Laplace Transforms. Use the rules in the attached table to compute the following Laplace transforms. (a) L [ t · e 2 t ] The table says that L [ t ] = 1 /s 2 and hence L [ t · e 2 t ] = L [ t ] s s - 2 = 1 ( s - 2) 2 . (b) L [ e 2 t · sin t ] The table says that L [sin t ] = 1 / ( s 2 + 1) and hence L [ e 2 t · sin] = L [sin t ] s s - 2 = 1 ( s - 2) 2 + 1 . (c) L [ t · sin t ] The table says that L [sin t ] = 1 / ( s 2 + 1) and hence L [ t · sin] = - d ds L [sin t ] = - d ds 1 ( s 2 + 1) = 2 s ( s 2 + 1) 2 . 7. Solve Using Laplace Transforms. Consider the equation x 0 ( t ) + x ( t ) = 2 sin t . (a) Find the partial fraction decomposition of 2 ( s +1)( s 2 +1) . We are looking for A, B, C so that 2 ( s + 1)( s 2 + 1) = A s + 1 + Bs + C s 2 + 1 2 ( s + 1)( s 2 + 1) = A ( s 2 + 1) + ( Bs + C )( s + 1) ( s + 1)( s 2 + 1) 2 = A ( s 2 + 1) + ( Bs + C )( s + 1) 0 s 2 + 0 s + 2 = ( A + B ) s 2 + ( B + C ) s + ( A + C ) . Comparing coefficients gives A + B = 0, B + C = 0 and A + C = 2, which implies that A = - B = C = 1. We conclude that 2 ( s + 1)( s 2 + 1) = 1 s + 1 + - s + 1 s 2 + 1 = 1 s + 1 - s s 2 + 1 + 1 s 2 + 1 . (b) Use Laplace transforms to solve the equation with x (0) = 0. Applying Laplace transforms gives x 0 ( t ) + x ( t ) = 2 sin t sX - x (0) + X = 2 s 2 + 1 ( s + 1) X = 2 s 2 + 1 X = 2 ( s + 1)( s 2 + 1)
5 X = 1 s + 1 - s s 2 + 1 + 1 s 2 + 1 x ( t ) = L - 1 1 s + 1 - L - 1 s s 2 + 1 + L - 1 1 s 2 + 1 x ( t ) = e - t - cos t + sin t. 8. Discontinuous Input. Consider the step function H ( t ) and the delta function δ ( t ). (a) Compute the partial fraction decomposition of 1 s ( s - 1) . We are looking for A, B such that 1 s ( s - 1) = A s + B s - 1 1 s ( s - 1) = A ( s - 1) + Bs s ( s - 1) 1 = A ( s - 1) + Bs Substituting s = 0 gives 1 = A (0 - 1) = - A and substituting s = 1 gives 1 = B , hence 1 s ( s - 1) = - 1 s + 1 s - 1 . (b) Use your answer from (a) to evaluate L - 1 h e - 3 s s ( s - 1) i If F ( s ) = L [ f ( t )] then L - 1 [ e - as · f ( t )] = H ( t - a ) f ( t - a ). In our case we have F ( s ) = 1 s ( s - 1) , which implies that f ( t ) = L - 1 1 s ( s - 1) = L - 1 - 1 s + 1 s - 1 = - L - 1 1 s + L - 1 1 s - 1 = - 1 + e t , and hence L - 1 e - 3 s s ( s - 1) = H ( t - 3) f ( t - 3) = H ( t - 3) ( - 1 + e t - 3 ) . (c) Use your answers from (a) and (b) to solve the equation x 00 ( t ) - x 0 ( t ) = δ ( t - 3) with initial conditions x (0) = x 0 (0) = 0. Applying Laplace transforms gives x 00 ( t ) - x 0 ( t ) = δ ( t - 3) s 2 X - sx (0) - x 0 (0) - ( sX - x (0)) = e - 3 s ( s 2 - s ) X = e - 3 s
6 X = e - 3 s s ( s - 1) x ( t ) = L - 1 e - 3 s s ( s - 1) x ( t ) = H ( t - 3) ( - 1 + e t - 3 ) . 9. First Order Linear System. Consider the linear system x 0 ( t ) = - x ( t ) + 2 y ( t ) , y 0 ( t ) = x ( t ) . (a) Find the eigenvalues and eigenvectors of the matrix - 1 2 1 0 . The eigenvalues are the roots of the characteristic equation: - 1 - λ 2 1 0 - λ = 0 ( - 1 - λ )(0 - λ ) - (1)(2) = 0 λ 2 + λ - 2 = 0 ( λ + 2)( λ - 1) = 0 λ = 1 , - 2 . The eigenvectors ( u, v ) for λ = 1 satisfy - 1 - 1 2 1 0 - 1 u v = 0 0 - 2 2 1 - 1 u v = 0 0 u v = any multiple of 1 1 The eigenvectors ( u, v ) for λ = - 2 satisfy - 1 + 2 2 1 0 + 2 u v = 0 0 1 2 1 2 u v = 0 0 u v = any multiple of 2 - 1 (b) Find the general solution of the linear system. The general solution is x ( t ) y ( t ) = c 1 1 1 e t + c 2 2 - 1 e - 2 t .
Your preview ends here
Eager to read complete document? Join bartleby learn and gain access to the full version
  • Access to all documents
  • Unlimited textbook solutions
  • 24/7 expert homework help
7 10. Second Order Linear System. Consider the linear system x 00 ( t ) = - 3 x ( t ) + 2 y ( t ) , y 00 ( t ) = x ( t ) - 2 y ( t ) . Here are the eigenvalues and eigenvectors of the coefficient matrix: - 3 2 1 - 2 1 1 = - 1 2 1 1 and - 3 2 1 - 2 2 - 1 = - 2 2 2 - 1 . (a) Use the given information to find the general solution of the system. The general solution is x ( t ) y ( t ) = a 1 1 1 cos t + b 1 1 1 sin t + a 2 2 - 1 cos(2 t ) + b 2 2 - 1 sin(2 t ) . (b) Find the specific solution with x (0) = x 0 (0) = y (0) = 0 and y 0 (0) = 1. Substituting t = 0 into x ( t ) and y ( t ) gives 0 0 = x (0) y (0) = a 1 1 1 + a 2 2 - 1 . This implies that 0 = a 1 + 2 a 2 and 0 = a 1 - a 2 , which has solution a 1 = a 2 = 0. Now we know that x ( t ) y ( t ) = b 1 1 1 sin t + b 2 2 - 1 sin(2 t ) . Taking derivatives and substituting t = 0 gives x 0 ( t ) y 0 ( t ) = b 1 1 1 cos t + 2 b 2 2 - 1 cos(2 t ) 0 1 = b 1 1 1 + 2 b 2 2 - 1 This implies that 0 = b 1 + 4 b 2 and 1 = b 1 - 2 b 2 , which has solution b 1 = 2 / 3 and b 2 = - 1 / 6. Hence the solution is x ( t ) y ( t ) = 2 3 1 1 sin t - 1 6 2 - 1 sin(2 t ) .